Ketamine and Electroconvulsive Therapy: A Case Report - Trindade Rei Rodrigues Pereira, Daniela Patricia; Rodrigues e Silva, Catarina; Proença Paulino, Ana Sofia; Alvim Gonçalves Pinto Rema, João Paulo (Journal of the Portuguese Society of Anesthesiology, 2022)
Electroconvulsive therapy (ECT) is the gold standard therapy for treatment-resistant depression and is usually performed under general anesthesia. A variety of induction agents may be used. Ketamine is an induction agent with increasing evidence suggesting an antidepressant effect. However, ketamine is known to produce psychotic symptoms and therefore its use has been avoided in psychosis. The authors explore the case of a 30-year-old man, who was diagnosed with affective psychosis with predominance of the negative symptoms. He had two major depressive episodes resistant to pharmacological therapy requiring long term permanence in the psychiatry ward and underwent twelve ECT sessions. Ketamine was the most frequently used induction agent. Its use was associated with longer electroconvulsive and motor responses as well as a decremental electrical charge. This treatment regimen led to a sustained remission of depressive symptoms and was not accompanied by psychotic or dissociative phenomena during the treatment and follow-up period.